(untitled) (Ustozlar uchun, 2025)
The effectiveness of foreign language teaching depends on the systematic interaction of three key curriculum components: the syllabus, the coursebook, and supplementary materials. The syllabus determines overall learning goals, specifies linguistic content, and defines assessment criteria. The coursebook organizes these goals into teachable units, providing structure and language input. Supplementary materials enrich the learning process by adapting lessons to learners’ diverse needs, learning styles, and classroom contexts. This article examines the roles, characteristics, and pedagogical alignment of these three components, arguing that effective coordination among them fosters communicative competence, enhances learner motivation, and supports curriculum coherence. Recommendations for educators and curriculum designers are provided to ensure that instructional resources remain learner-centered and responsive to contemporary educational demands.